Protocols for perioperative management of direct oral anticoagulants in hospitals: opportunities for improvement. (2nd January 2023) - Mitrovic, Darko; van Elp, Margriet; Veeger, Nic; Lameijer, Heleen; Meijer, Karina; van Roon, Eric
Abstract: Objectives: To investigate and describe the protocolized perioperative management in patient using Direct oral anticoagulants (DOACs) in Dutch hospitals. Methods: Between August and December 2020, a nationwide survey in 70 hospitals in the Netherlands was conducted. We asked hospital pharmacists to submit their protocols for perioperative management of DOAC (apixaban, dabigatran, edoxaban and rivaroxaban) users. The protocols were assessed for a number of parameters divided into categories: interruption and restart timetables DOACs for elective procedures, criteria for the start of an urgent procedure without antidotes, criteria for the use of antidotes and advised antidotes for urgent procedures. Results: A total of 49 hospitals (70%) sent a protocol for perioperative management of DOACs. Two pairs of protocols were identical because hospitals cooperated closely, leaving 47 individual protocols for analysis. Thirty-five of these protocols contained a policy for both elective and urgent procedure; five protocols contained only a policy for elective and seven only for urgent procedures. In protocols for elective procedure, we found great variation in interruption and restart timetables intended for patients with renal impairment (Estimated Glomerular Filtration Ratio < 80 ml/min). In case of urgent procedures, there is variation in choice of antidote, criteria for administration of an antidote and antidote dosing. Conclusion: This study provides an overview of the current state of the perioperative protocols in the Netherlands in patients treated with direct oral anticoagulants. Protocols are often not complete and show important and unwanted variation. We have found that national guidelines do not provide unambiguous advice on all points (urgent procedures) and are therefore often elaborated at a local level. The results of this research can help in improving and harmonizing the perioperative protocols on a national level.